2019
DOI: 10.1080/08037051.2019.1696180
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total calcium concentration is associated with blood pressure and systemic vascular resistance in normotensive and never-treated hypertensive subjects

Abstract: 2020) Plasma total calcium concentration is associated with blood pressure and systemic vascular resistance in normotensive and never-treated hypertensive subjects, Blood Pressure, 29:3, 137-148, ABSTRACT Purpose: The underlying causes of primary hypertension are not fully understood. Evidence on the relation of plasma calcium concentration with blood pressure (BP) is inconsistent and relies largely on studies utilizing office BP measurements in populations using cardiovascular drugs. In many studies adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Changes in calcium metabolism may influence BP 60 , and induce alterations in the components of the reninangiotensin system in the vasculature 61 . Moreover, vitamin D receptor activation downregulates the synthesis of renin in the juxtaglomerular cells and influences the expression of other components of the renin-angiotensin system in the kidney 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in calcium metabolism may influence BP 60 , and induce alterations in the components of the reninangiotensin system in the vasculature 61 . Moreover, vitamin D receptor activation downregulates the synthesis of renin in the juxtaglomerular cells and influences the expression of other components of the renin-angiotensin system in the kidney 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that plasma total calcium concentration was directly linked to the level of BP via elevated systemic vascular resistance (SVR) in normotensive and hypertensive subjects without antihypertensive agents [22]. In the present cross-sectional study we examined whether plasma PTH, a key regulator of calcium levels [23], is associated with central BP and its haemodynamic determinants in 622 normotensive or never-treated hypertensive subjects, who had plasma PTH and calcium concentrations predominantly within the normal range.…”
Section: Introductionmentioning
confidence: 92%
“…Subjects were selected from an ongoing investigation on haemodynamics in primary and secondary hypertension (DYNAMIC study, clinical trial registration NCT01742702), currently comprising 1349 subjects. The enrolment has been previously described [22]. The study was approved by the ethics committee of the Tampere University Hospital (code R06086M) and the Finnish Medicines Agency (Eudra-CT number 2006-002065-39), and it complies with the Declaration of Helsinki.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations